Émigré literature & the spiritual revolution - Altabaa, Homam (2020)
Émigré writers, commonly acknowledged as leading figures in modern Arabic literature and respected writers in American literature, have introduced various spiritual aspects throughout their works. This study seeks to examine these aspects through comparative and thematic approaches. The focus is on Kahlil Gibran as the leading figure in the mahjar literary school.